An Amperometric Biosensor For Hg(II) Based On Urease/AlginateÃ¢â¬âChitosan Membrane Modified Screen Printed Carbon Electrode - Rochmad Kris Sanjaya; Nurul Ismillayli; Dhony Hermanto (Jurnal Pijar Mipa, 2019)
A screen-printed three-electrode system is fabricated to prepare a novel screen-printed biosensor for rapid determination of Hg(II) in aqueous solution. The amperometric biosensor is prepared by entrapping urease in alginateÃ¢â¬âchitosan membrane to modify the screen-printed carbon electrode. The urease/alginateÃ¢â¬âchitosan membrane for Hg(II) had optimum measurement conditions at work potential of -0.15 V, pH of 7, urea concentration of 75 mM, response time of 8 seconds, inhibition time of 7 minutes and temperature of 25 ÃÂ°C. The resulted biosensor characteristic were found to have the range concentration of Hg(II) ion between 40-90 ppb with the detection limit I10% was 66.45 ppb, the coefficient of variance (Cv) was 0.8%, and reactivation was 5 times reuse.